Analisis Penjadwalan Proses Packing Arumanis Dengan Menggunakan Metode CDS (Campbell Dudeck Smith) dan NEH (Nawas, Enscore,and HAM) Studi Kasus di UMKM Arumanis Haji Ardi Sleman : Penjadwalan Proses Packing Arumanis Dengan Metode CDS dan NEH - Puji Asih; Iva Mindhayani; Tatak Prakasa (Jurnal Rekayasa Industri (JRI), 2022)
ABSTRACT UMKM Arumanis Haji Ardi is a household industry that produces sweet arum located in Berbah, Sleman, D.I. Yogyakarta. Companies often have difficulty meeting consumer demand in a timely manner. The problem of improper delivery schedule of the order is caused by scheduling the packing process which often experiences delays. The purpose of this research is to find out the comparison of completion time, and know the methods that can complete the production process at the shortest. Campbell Dudeck Smith's scheduling method is a scheduling process based on the smallest working time, and having the advantage of being able to provide many scheduling alternatives. The Nawas, Enscore, and Ham method is that scheduling or assignments with a larger total process time should be given greater priority than the smaller total process time. Given the importance of the proper scheduling process, the author wants to do a scheduling analysis of the Packing process using the Campbell Dudeck Smith and Nawas, Enscore, and Ham methods. The results of the research comparison of scheduling time applied by the company have a sequence of 1-2-3-4 with a makepan of 44,395,142.92 seconds. Campbell Dudeck Smith was 4-3-2-1 with 44,335,921.922 seconds. Scheduling with nawas, Enscore, and Ham method has a sequence of 2-1-3-4 with makespan 44,515.921.12 seconds. The most appropriate method used is the Campbell Dudeck Smith method because it has the smallest makespan which is 44,335,921.12 seconds with a percentage of comparison between cds and NEH methods is 0.4%. Keywords: Scheduling, Packing, Campbell Dudeck Smith, Nawas, Enscore, and Ham